Clinical outcome after endoscopic resection for superficial pharyngeal squamous cell carcinoma invading the subepithelial layer - Satake, Hironaga; Yano, Tomonori; Muto, Manabu; Minashi, Keiko; Yoda, Yusuke; Kojima, Takashi; Oono, Yasuhiro; Ikematsu, Hiroaki; Aoyama, Ikuo; Morita, Shuko; Miyamoto, Shinichi; Fujii, Satoshi; Yoshizawa, Akihiko; Ochiai, Atsushi; Hayashi, Ryuichi; Kaneko, Kazuhiro (Endoscopy, 2015)
Background and study aims: The curability of endoscopic resection for superficial pharyngeal squamous cell carcinoma (SPSCC) has not been fully elucidated, particularly for lesions invading the subepithelial layer, which carry the risk of metastasis. The aim of this study was to evaluate the curative potential of endoscopic resection for SPSCC invading the subepithelial layer.Patients and methods: From June 2002 to July 2010, 198 SPSCCs in 176 consecutive patients were treated by endoscopic resection at two tertiary referral centers. Selection criteria were initial endoscopic resection, histologically proven squamous cell carcinoma invading the subepithelial layer, no lymph node or distant metastasis before endoscopic resection, and no prior treatment for pharyngeal squamous cell carcinoma. Endoscopic resection was performed under general anesthesia. Long-term survival and clinical outcomes were retrospectively evaluated. Results: Among 176 consecutive patients, 50 lesions in 47 patients (all male; median age 64 years) were histologically diagnosed from endoscopic resection specimens as having subepithelial invasion. Median tumor thickness was 1000 μm (range 200 – 10 000 μm). Six patients developed local recurrence (13 %; 95 % confidence interval [CI] 3.1 % – 22.4 %), and all were cured with organ-preserving intervention. After a median follow-up period of 71 months (range 27 – 116 months), one patient (2 %; 95 %CI 0 – 6.3 %) developed neck lymph node metastasis. A total of 14 patients (30 %) were followed for 5 years or more, and 5-year overall survival and disease-specific survival rates were 84.5 % (95 %CI 73 % – 96 %) and 100 %, respectively. Conclusions: Endoscopic resection has curative potential as a minimally invasive treatment option for SPSCC that invades the subepithelial layer.